Elucidating the degradation mechanism of 0.5Gd2Zr2O7·0.5TRPO under multi-energy He ion irradiation. Issue 9 (August 2023) - Duan, Junjing; Huang, Zhangyi; Hu, Xunxiang; Wang, Haomin; Zhang, Yutong; Yang, Yao; Mertsoy, Esra Y.; Wu, Di; Qi, Jianqi; Lu, Tiecheng
Abstract: Gd2 Zr2 O7 has long been considered as one of the most promising waste forms and has attracted broad interest in the field of nuclear waste immobilization. This work utilizes multi-energy He-irradiation to study the microstructural and helium bubble evolution of Gd2 Zr2 O7 immobilizing with the final waste after partitioning high-level liquid waste by using the trialkyl phosphide (TRPO waste, the waste load is 50 wt%) in an experimentally feasible time frame. Interestingly, at less than 40 nm below the He-irradiated surface ( Region I ), there are a significant number of well-aligned large spherical He bubbles with diameters ranging from 5 to 25 nm and a severely amorphous structure. The mechanism of these novel phenomena may be related to enhanced migration rate of vacancies by high electronic energy loss, promoting the combination of vacancies with relatively high-density He atoms, suppressing the recombination-annihilation of vacancies and interstitial atoms, thus accelerating the irradiation amorphization.